Peran Shared Leisure Satisfaction dan Conflict Resolution Terhadap Co- Parenting pada Pasangan Dual Earner Di Gereja X - Sandy, Azarine Benita; Setiawan, Jenny Lukito (Psychopreneur Journal, 2020)
This study was conducted to determine the role of shared leisure satisfaction and conflict resolution on co-parenting in dual earner couples in church X. The hypothesis in this study is that shared leisure satisfaction and conflict resolution play a significant role in co-parenting. Using quantitative research methods with correlational designs. The subjects in this study were 90 dual earner congregants in Church X in Banyuwangi because a phenomenon that was found to be suitable for the population was obtained by accidental sampling technique. Data analysis using multiple linear regression test showed that shared leisure satisfaction and conflict resolution contribute to co-parenting in dual earner pairs (F = 23,164; p < 0,05), for conflict resolution it plays a role in co-parenting (t = 4,928; p <0,05 ), so also shared leisure satisfaction contributes to co-parenting (t = 4,347; p < 0,05). The total effective contribution of the two variables is 34,7% (R2 = 0,347). The conclusion of this study is that shared leisure satisfaction and conflict resolution play a role in co- parenting in dual earners.